EHR prescription for small, medium, and large hospitals: an exploratory study of Texas acute care hospitals. (18th October 2012) - Mitchell, Stacy; Yaylacicegi, Ulku
Hospitals invest in information technology to lower costs and to improve quality of care. With presidential leaders backing an in place policy that requires Electronic Health Records (EHRs) to be implemented in all hospitals by 2014 and the unveiling of a $1.2 billion grant for these systems, it is essential to understand the operational impacts of EHRs. This study explores EHRs in a hospital environment and investigates their relationship to quality of care and patient safety. EHRs are categorised into four functional groups: patient information data, results management, order entry, and decision support. This new knowledge will provide a better understanding of the relationship between EHRs and operational outcomes by showing the impact of various EHR functions on patient safety and quality of care.